2013
DOI: 10.1039/c3sm51017d
|View full text |Cite
|
Sign up to set email alerts
|

Formation and properties of wormlike micelles in solutions of a cationic surfactant with a 2-hydroxypropoxy insertion group

Abstract: The rheological properties of aqueous solutions of a cationic surfactant, 3-hexadecyloxy-2-hydroxypropyl trimethyl ammonium bromide (R 16 HTAB), and its mixed solution system with sodium salicylate (NaSal) have been studied by using steady state and frequency sweep rheological measurements. The microstructure of the formed wormlike micelles has been ascertained by transmission electronic microscopy and 1 H NMR technology. The effects of the surfactant concentration, added salt, temperature and different counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 51 publications
(70 reference statements)
1
19
0
Order By: Relevance
“…These tight packing of ILBSs monomers may lead to the formation of large elongated shaped micelles with increased viscosity of the solution. This increased viscosity may be attributed to the transition of spherical micelle to non‐spherical micelles such as rod like or worm like micelles, as observed in various ionic surfactants and ILBSs in the presence of organic salts . Recently, Kusano et al., had reported that with increasing the concentration of the NaSal, the spherically shaped micelles of star‐type trimeric surfactant transformed into the wormlike micelles with increased viscosity .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…These tight packing of ILBSs monomers may lead to the formation of large elongated shaped micelles with increased viscosity of the solution. This increased viscosity may be attributed to the transition of spherical micelle to non‐spherical micelles such as rod like or worm like micelles, as observed in various ionic surfactants and ILBSs in the presence of organic salts . Recently, Kusano et al., had reported that with increasing the concentration of the NaSal, the spherically shaped micelles of star‐type trimeric surfactant transformed into the wormlike micelles with increased viscosity .…”
Section: Resultsmentioning
confidence: 94%
“…The extent of the growth and dimensions mainly depend on the nature and concentration of the added counter ions . Addition of NaSal into the micellar solutions of C 14 VnImBr and C 16 VnImBr reduces the electrostatic repulsion between the cationic head group, whereas the aromatic part of the Sal anion penetrates into the more hydrophobic region of the micelles, the micellar core, leading to the tight packing of ILBSs monomers and increases the aggregation number of micelle; finally induces the transition of the spherically shaped aggregates probably into rod like or wormlike aggregates ,,. Analogy to the present system; in the cholesterol/surfactant system,, cholesterol molecule got incorporated in the micellar structure, changed the radius of the curvature and transform the spherical micelles into vesicles.…”
Section: Resultsmentioning
confidence: 99%
“…One of the reasons for these upfield shifts is attributed to the interaction between the quaternary ammonium groups of CTA + and the benzene ring of aromatic compounds. 38–40 To verify this, we conducted 19 F NMR spectroscopy of FSal. The FSal signal appeared at −105.0 ppm, and it shifted downfield with increasing CTAB concentration to −104.5 ppm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the recent years, the self-assembly behaviors of surfactants have been of particular interest in numerous industrial processes. The surfactants can self-assemble to form aggregates with different microstructures and shapes in aqueous solution, such as spherical micelles, rodlike micelles, wormlike micelles, vesicles, lamellar phases, and liquid crystals. Among these aggregates with various morphologies and structures, considerable attention from both theoretical research studies and industrial applications has been focused on wormlike micelles because of their unique viscoelastic behaviors and wide potential applications. , Wormlike micelles show remarkable viscoelastic properties analogous to those of polymer solutions.…”
Section: Introductionmentioning
confidence: 99%